2007
DOI: 10.1063/1.2804008
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution synchrotron x-ray diffraction study of Zr-rich compositions of Pb(ZrxTi1−x)O3 (0.525⩽x⩽0.60): Evidence for the absence of the rhombohedral phase

Abstract: Results of Rietveld analysis of the synchrotron XRD data on Pb(Zr x Ti 1-x )O 3 (PZT) for 0.525≤x≤0.60 are presented to show the absence of rhombohedral phase on the Zr-rich side of the morphotropic phase boundary (MPB). Our results reveal that the structure of PZT is monoclinic in the Cm space group for 0.525≤x≤0.60. The nature of the monoclinic distortion changes from pseudo-tetragonal for 0.525≤x≤0.54 to pseudorhombohedral for x>0.54.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…To seek answer to this contentious issue, it is necessary to understand the subtle differences between three different types of monoclinic phases that exist or may exist at room temperature: (i) Firstly, there is a pseudotetragonal monoclinic phase with Cm space group for which the (200) pc peak is a doublet. As shown by Singh et al 14 and Pandey et al 15 using Rietveld analysis of high resolution synchrotron X-ray powder diffraction (SXRD) data, this phase exists over a very narrow composition range 0.520 x<0.530 at room temperature, as confirmed by refinements. This is the phase discovered by Noheda et al 16,17 to which the tetragonal phase transforms below room temperature for x=0.520.…”
Section: Introductionmentioning
confidence: 86%
“…To seek answer to this contentious issue, it is necessary to understand the subtle differences between three different types of monoclinic phases that exist or may exist at room temperature: (i) Firstly, there is a pseudotetragonal monoclinic phase with Cm space group for which the (200) pc peak is a doublet. As shown by Singh et al 14 and Pandey et al 15 using Rietveld analysis of high resolution synchrotron X-ray powder diffraction (SXRD) data, this phase exists over a very narrow composition range 0.520 x<0.530 at room temperature, as confirmed by refinements. This is the phase discovered by Noheda et al 16,17 to which the tetragonal phase transforms below room temperature for x=0.520.…”
Section: Introductionmentioning
confidence: 86%
“…We observed significant anisotropic peak broadening in our BNT-PT samples for the compositions close to MPB. It is well known for the MPB systems like PZT [3,49] and PMN-PT [48] that anisotropic broadening of the diffraction profiles is 12 observed for the rhombohedral as well as tetragonal compositions close to the MPB.…”
Section: G Discussionmentioning
confidence: 99%
“…Consequently, a new x-T phase diagram of the PZT system was proposed (Pandey & Ragini, 2003), and more recently (Woodward et al, 2005;Pandey et al, 2008), a revised phase diagram was suggested including a region of monoclinic phases with Cm and Cc symmetries at compositions corresponding to the MPB. In addition to this context, more recent studies (Singh et al, 2007) suggest the presence of a monoclinic phase on the PZT system with the Cm space group instead of the rhombohedral phase with the R3m space group for Zr-rich compositions (0.40 ≤ x ≤ 0.475). Thus, the limits for the monoclinic phase existence in the x-T phase diagram of the PZT system are still open for discussion.…”
Section: Structure Of Pmn-pt Compositions At the Mpbmentioning
confidence: 99%